2003
DOI: 10.1007/s11746-003-0836-4
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid content in ground corn by NIR spectroscopy with an indirect calibration method

Abstract: Developing corn hybrids with improved FA profiles is important in providing products with enhanced nutritional characteristics. To support this effort, rapid screening methods are needed to track the various traits of interest. In using NIR methods, calibrations are based on an assumed linear relationship between the concentration of the analyte of interest and the absorbance of the sample. Although this point seems obvious, this linear relationship does not exist when using GC analysis as a reference method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(15 reference statements)
3
8
0
Order By: Relevance
“…Since NIR calibration development is based on the Beer-Lambert's Law, i.e., that the absorbance varies linearly with the analyte concentration, it would make sense that better statistical results should be achieved with a calibration based on absolute FA content. These results are similar to those achieved with the oleic acid content in ground corn (17).…”
Section: Resultssupporting
confidence: 89%
“…Since NIR calibration development is based on the Beer-Lambert's Law, i.e., that the absorbance varies linearly with the analyte concentration, it would make sense that better statistical results should be achieved with a calibration based on absolute FA content. These results are similar to those achieved with the oleic acid content in ground corn (17).…”
Section: Resultssupporting
confidence: 89%
“…These results are partially in agreement with Wright et al (2003) showing that the nonlinear relationship between fatty acid content and absorbance could be corrected by using absolute concentrations. However, the correction to relative concentrations by the NIRS-predicted oil content degraded the calibration precision.…”
Section: Discussionsupporting
confidence: 91%
“…The use of absolute fatty acid concentration was suggested by Dr. Steven Wright, Pioneer Hi-Bred International Inc. [34] because of the nature of NIRS to determine content by counting molecules. Soybean oil calibrations were developed on the fatty acid calibration samples.…”
Section: Fatty Acids Expressed In Absolute Concentration and Correctementioning
confidence: 99%
“…In fact, the results obtained in a study estimating oleic acid content on maize flour suggested that whole product computation of oleic acid content had a positive effect on the estimation power of the model (Wright and Hagen 2003). Additionally, computing the oleic acid content on a whole product level (i.e., multiplying oleic acid by oil content) may yield better results.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on general quality traits in maize are available in which the researchers simultaneously evaluated the effects of sample type and statistical method on developing calibration models (Orman and Schumann 1991). The studies on the analysis of maize fatty acids with NIR (Wright and Hagen 2003;Baye et al 2006;Yang et al 2009) are rather limited compared with studies on the general quality traits of maize kernel (Weinstock et al 2006;Jiang et al 2007;Spielbauer et al 2009;Tallada et al 2009;Egesel and Kahrıman 2012;Fassio et al 2015). Most experiments used one type of sample (either intact kernel or flour) and did not attempt any comparison between the models developed with different chemometric methods.…”
mentioning
confidence: 99%